Witnesses of a shipwreck. Books from the family library of Huarte on the ancient collection of the library of the Public University of Navarre - Panizo Santos, Ignacio (Huarte de San Juan. Geografía e Historia, 2016)
The author identifies 562 printed books and brochures that belonged to the Huarte family. These books were acquired by the Public University of Navarra in 1997. The majority of its content is of Law and Pedagogy.
Keywords: Family Huarte; Pamplona; Navarre; Library of the Public University of Navarre; History of libraries